Job Embeddedness: a Strategy to Reduce Voluntary Turnover Intention - Ratnawati, Alifah; Sudarti, Ken; Mulyana, Mulyana; Mubarok, M Husni (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2020)
This study examines the relationship between Job Embeddedness and Job Insecurity to voluntary turnover intention and job performance. The sample of this study were 209 respondents from permanent or contract employees who worked as secretaries, clerical or administrative personnel in government or private offices in Central Java, Indonesia. This study used Structural Equation Modelling (SEM) for hypothesis testing. Result of this job insecurity cannot be used to predict voluntary turnover intention or job performance. Job embeddedness is divided into three types, namely job embeddedness link, job embeddedness fit, and job embeddedness sacrifice. Job Embeddedness link and Job Embeddedness fit have no effect on voluntary turnover intention, but they can be used to predict job performance. In contrast, Job embeddedness sacrifice has an effect on voluntary turnover intention but cannot be used to predict job performance. Voluntary turnover intention proved able to be used to predict job performance.